Synthesis and biological evaluation of novel pentanediamide derivatives as S-adenosyl-l-homocysteine hydrolase inhibitors. (15th September 2022) - Lv, Yu-Bin; Chen, Cong; Yu, Qi-Ming; Lyu, Liang; Peng, Yan-Fen; Tan, Xiang-Duan
Graphical abstract: Abstract: A series of novel pentanediamide derivatives were designed, synthesized and evaluated as S -adenosyl- l -homocysteine hydrolase (SAHase) inhibitors in this study. Some compounds showed good inhibitory activity against SAHase. The optimal compound 7i showed good inhibitory activity against SAHase with IC50 value of 3.58 ± 0.19 μM, cytotoxicity with IC50 values ranging from 13.16 ± 1.44 to 21.23 ± 0.73 μM against four tumor cell lines (MCF-7, A549, MGC-803, Hela) and very weak cytotoxicity (IC50  = 84.22 ± 1.89 μM) on normal LO2 cells. In addition, compound 7i showed potency against respiratory syncytial virus with EC50 value of 27.4 μM and selectivity index of 6.84. Further molecular simulation study suggested that compound 7i had good ADMET properties, and strongly binds to the active site of SAHase. In summary, compound 7i could serve as a new lead compound for further screening novel non-adenosine SAHase inhibitors.